The Influence of Social Media Marketing, Brand Image, and Product Knowledge on Public Interest In using The Livin by Mandiri Application - Shafira Adzra; Marlina Widiyanti; Ahmad Maulana; Dessy Yunita (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This study was conducted to determine the effect of social media marketing, brand image and product knowledge on public interest in using the Livin by Mandiri application. This research uses a qualitative approach. The population in this study were all customers of PT Bank Mandiri (Persero), Tbk in Palembang City who used the Livin by Mandiri application in 2024 with a total of 220,868 customers. The sample in this study was taken from the total population of all customers at PT Bank Mandiri (Persero), Tbk in Palembang City as many as 100 respondents. The results of multiple linear regression analysis show that social media marketing, brand image and product knowledge have a positive and significant effect on public interest in using. Social media marketing, it is hoped that the admin in charge of managing social media will be able to respond quickly to customer needs. Brand image, it is hoped that improvements in providing evaluations to employees, especially in the customer service section, will provide good, polite, calm, neat and in accordance with the SOP. Product knowledge, it is expected to continue to maintain application stability and improve the quality of the Livin by Mandiri application so that customers can always use it.